Les enfants de l'avenir radieux - Sulea, Gabriela (France, 2010)
Analyzing the texts and pictures of Romanian textbooks used during the Ceausescu times, this film invites you to discover the ideological indoctrination of young children under the oppressive communist regime of Nicolae Ceausescu's Romania.
Verzio Film Festival Submission
Verzio Film Festival Submission